2022
DOI: 10.1093/cid/ciac123
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in coronavirus disease 2019 (COVID-19) Vaccination Rates Among Adolescents in Massachusetts: A Cross-sectional Study

Abstract: Background The COVID-19 pandemic has disproportionately affected more socioeconomically disadvantaged persons and areas. We sought to determine how certain sociodemographic factors were correlated to adolescents’ COVID-19 vaccination rates in towns and cities (“communities”) in the Commonwealth of Massachusetts. Methods Data on COVID-19 vaccination rates were obtained over a 20-week period from March 30, 2021 to August 10, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Parents with lower SES and belonging to minority groups were less likely to vaccinate their children than their more privileged counterparts. [18][19][20][21][22] This phenomenon has been observed also for other types of vaccines. Studies on children immunisation against diseases such as measles, mumps and rubella (MMR-vaccine) and tetanus, diphtheria and pertussis (DPT-vaccine), indicated that children vaccination status depended, among other things, of parental education, household income and parents being born in another country.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 61%
See 3 more Smart Citations
“…Parents with lower SES and belonging to minority groups were less likely to vaccinate their children than their more privileged counterparts. [18][19][20][21][22] This phenomenon has been observed also for other types of vaccines. Studies on children immunisation against diseases such as measles, mumps and rubella (MMR-vaccine) and tetanus, diphtheria and pertussis (DPT-vaccine), indicated that children vaccination status depended, among other things, of parental education, household income and parents being born in another country.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 61%
“…Furthermore, one of the studies showed that as income levels decreased, the likelihood of adolescent vaccination correspondingly declined 20 . Demographic regions characterised by higher poverty rates and lower SES had a higher proportion of Black and Hispanic individuals, and thus children from these ethnic backgrounds were less likely to be vaccinated than White or Asian children 18,20,21 . Additionally, children with parents with a master's degree exhibited a 47% higher probability of vaccination, compared to those born to parents with lower education levels 18 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, this study showed that high-income counties have higher vaccination rates. A previous study also indicated that county-level income was positively associated with COVID-19 vaccination rates [26]. Fourth, counties with a higher percentage of residents with limited English proficiency had higher vaccination rates (regression coefficient 0.24).…”
Section: Discussionmentioning
confidence: 73%